Extracellular vesicles of Norway spruce contain precursors and enzymes for lignin formation and salicylic acid - Kankaanpää, Santeri; Väisänen, Enni; Goeminne, Geert; Soliymani, Rabah; Desmet, Sandrien; Samoylenko, Anatoliy; Vainio, Seppo; Wingsle, Gunnar; Boerjan, Wout; Vanholme, Ruben; Kärkönen, Anna (Oxford University Press (OUP), 2024)
Lignin is a phenolic polymer in plants that rigidifies the cell walls of water-conducting tracheary elements and support-providing fibers and stone cells. Different mechanisms have been suggested for the transport of lignin precursors to the site of lignification in the cell wall. Extracellular vesicle (EV)-enriched samples isolated from a lignin-forming cell suspension culture of Norway spruce (Picea abies L. Karst.) contained both phenolic metabolites and enzymes related to lignin biosynthesis. Metabolomic analysis revealed mono-, di-, and oligolignols in the EV isolates, as well as carbohydrates and amino acids. In addition, salicylic acid (SA) and some proteins involved in SA signaling were detected in the EV-enriched samples. A proteomic analysis detected several laccases, peroxidases, β-glucosidases, putative dirigent proteins, and cell wall-modifying enzymes, such as glycosyl hydrolases, transglucosylase/hydrolases, and expansins in EVs. Our findings suggest that EVs are involved in transporting enzymes required for lignin polymerization in Norway spruce, and radical coupling of monolignols can occur in these vesicles.
Keywords: lignin formation; extracellular vesicles; Norway spruce